The Regulation of Axon Diameter: From Axonal Circumferential Contractility to Activity-Dependent Axon Swelling - Costa, Ana Rita; Pinto-Costa, Rita; Sousa, Sara Castro; Sousa, Mónica Mendes (Frontiers in Molecular Neuroscience, 2018)
In the adult nervous system axon caliber varies widely amongst different tracts. When considering a given axon, its diameter can further fluctuate in space and time, according to processes including the distribution of organelles and activity-dependent mechanisms. In addition, evidence is emerging supporting that in axons circumferential tension/contractility is present. Axonal diameter is generically regarded as being regulated by neurofilaments. When neurofilaments are absent or low, microtubule-dependent mechanisms can also contribute to the regulation of axon caliber. Despite this knowledge, the fine-tune mechanisms controlling diameter and circumferential tension throughout the lifetime of an axon, remain largely elusive. Recent data supports the role of the actin-spectrin-based membrane periodic skeleton and of non-muscle myosin II in the control of axon diameter. However, the cytoskeletal arrangement that underlies circumferential axonal contraction and expansion is still to be discovered. Here, we discuss in a critical viewpoint the existing knowledge on the regulation of axon diameter, with a specific focus on the possible role played by the axonal actin cytoskeleton.